A Survey on Seasonal Symptoms in Subjects with and Without Allergic Rhinitis Diagnosis - Arthur Helbling; Mathilde Foglierini; Victor Colin; Yannick D. Muller; Elisabeth Schuller; Annika Stern; Kaspar Strub (Allergies)
In Switzerland, only scarce data are available on the prevalence and treatment of allergic rhinitis. Although the presence of AR symptoms in temporal relation to the respective aeroallergen is indicative, still a substantial number of affected individuals are deemed underdiagnosed and potentially undertreated. A national online survey was conducted for consecutive participants with AR symptoms in medical practices irrespective of diagnosis, therapy, or the reason for the visit. Univariate and multivariate regression analyses were performed, as well as multiple correspondence analysis for participants with allergic rhinitis diagnosis (ARwD) and without diagnosis (ARwoD). A total of 392 of 637 participants with rhinitic symptoms self-reported an AR diagnosis with a symptom onset more than 5 years ago in 74%. Despite treatment, up to one-third of participants with ARwD had persistent severe symptoms. Asthma was reported more frequently in participants with ARwD (148/392) than with ARwoD (26/245), (42% vs. 12%, p < 0.001, q < 0.001). Allergologists were consulted more often by participants with ARwD (106/392; 30% vs. 3/245; 2%), while more participants with ARwoD visited pharmacies for treatment advice (40/392; 11% vs. 57/245; 40%). The coexistence of AR and asthma with severe symptoms is a specific phenotype with difficult to treat nasal symptoms, amongst others. Hence, appropriate diagnosis and treatment of suspected and diagnosed AR should be prioritized, especially, but not limited to, patients with AR and asthma.